The Reality of Sustainable Development in the Light of Climate Change - Ben Muchairah, Mohamed (Journal of Legal Studies and Researches, 2023)
The Rapid civilized development has made humanity realize that living in safety ‎requires a healthy environment, a balanced biodiversity, and a stable climate, to devote the ‎requirements of sustainable development, but climate change, which made the application of his theory a matter that required a lot Challenges.